ANALISIS DETERMINAN PEMBANGUNAN SUMBER DAYA MANUSIA DI PULAU MADURA PASCA PEMBANGUNAN JEMBATAN SURAMADU - Sa'adah, Nailus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Humans are objects as well as subjects development. So that human development is an important factor in achieving community welfare. One of the areas in East Java Province, namely Madura Island, has the lowest HDI rate and the highest poverty rate in East Java. This study aims to determine what factors influence human development on Madura Island from 2010-2020. Where the independent variables used are income per capita, poverty, government social spending, and population density. Meanwhile, the dependent variable that measures human development is the Human Development Index (IPM). This research uses panel data regression analysis method with Common Effect Model (CEM) method. The statistical analysis process uses a tool, namely eviews-9. So that the results of the study are that the income variable per capita has a positive and significant effect on the HDI on Madura Island, the poverty variable has a negative and significant effect on HDI on Madura Island, and the variables of government social expenditure and population density have a positive but not significant effect on HDI on Madura Island. Keywords: Human Development, HDI, per capita income, Poverty, Government Social Expenditure, Population Density, Madura Island, Panel Data.